The positive correlation between serum malondialdehyde levels with vitiligo severity and activity - I Gusti Ayu Agung Praharsini; Anak Agung Gde Putra Wiraguna; Putu Nila Wardhani Batan (DiscoverSys Inc, 2019)
Background: There are several theories that suggest melanocyte death in vitiligo, one example is oxidative stress theory. Oxidative stress primarily manifested by lipid peroxidation ultimately produce malondialdehyde. Malondialdehyde is a stable marker to assess an oxidative stress event. The correlation between serum malondialdehyde levels and vitiligo severity and activity remained controversial in previous studies.Objective: This study aimed to verify whether or not the serum MDA levels are positively correlated with vitiligo severity and activity.Methods: This study was an analytical cross-sectional study. which involved 64 subjects with vitiligo and 20 subjects without vitiligo. Serum MDA levels were measured to mark an oxidative stress event, whereas the severity and activity of vitiligo were clinically assessed with vitiligo area severity index (VASI) and vitiligo disease activity (VIDA) scoring system.Results: Total 64 subjects with vitiligo and 20 subjects without vitiligo participated in this study. Serum MDA mean levels of vitiligo subjects were significantly higher compared to subjects without vitiligo (p<0.05). Serum MDA levels had a strong positive correlation with VASI score (r=0.761; p<0.01). The strong positive correlation found between serum MDA levels with vitiligo activity assessed by VASI score in vitiligo subjects (r=0.609; p<0.01), and high serum MDA levels increased the risk for developing vitiligo (PR=7.62; 95% CI: 2.49-23.30; p<0.01). Serum MDA levels influenced vitiligo as much as 10.1%, meanwhile the remaining 89.9% were influenced by other variables apart from high serum MDA levels out of this study (R2=0.101; p<0.05).Conclusion: Serum MDA levels were positively correlated with vitiligo severity and activity, and high serum MDA levels increased the risk of developing vitiligo.